Knowledge of Radiology students about the improper disposal of radiographic films (Research, Society and Development, 2024)
The paper briefly discusses the use of radiographic films in diagnostic imaging exams, highlighting the potential future harms related to heavy compounds used in producing radiographic films, which are used for printing radiographs. These harmful effects are associated with the chemicals in the film used during the printing process. This study aims to demonstrate the magnitude of the proportionality that an X-ray film can cause to the environment when adequate disposal is not carried out, as substances containing heavy metals that harm human health are applied during the film manufacturing process. The study's results showed many responses from participants, which emphasized the lack of knowledge regarding the type of waste and the correct disposal methods by many individuals. To achieve this goal, a field survey was conducted, initially using a semi-structured questionnaire to assess the knowledge of students in the field who have direct contact with radiology accessories and materials, as well as practices in facilities that handle radioactive waste. The study proposed the establishment of collection points where the community could dispose of such materials in specific locations for future recycling.